The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s11999-014-3603-0
|View full text |Cite
|
Sign up to set email alerts
|

The Chitranjan Ranawat Award: Periarticular Injections and Femoral & Sciatic Blocks Provide Similar Pain Relief After TKA: A Randomized Clinical Trial

Abstract: Background Two of the more common methods of pain management after TKA are peripheral nerve blocks and intraarticular/periarticular injections. However, we are not aware of any study directly comparing the commonly used combination of a continuous femoral block given with a single-shot sciatic block with that of a periarticular injection after TKA. Questions/purposes This randomized clinical trial compared a combined femoral and sciatic nerve block with periarticular injection as part of a multimodal pain prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(96 citation statements)
references
References 37 publications
(84 reference statements)
6
87
1
Order By: Relevance
“…Local infiltration anesthesia (LIA) has been gaining focus in recent years, as several wellconducted studies had indicated the potential benefits postoperatively [21,22]. LIA consists of a mixture of medications that include long-acting anesthetic, NSAIDs and epinephrine.…”
Section: Anesthesia Approachmentioning
confidence: 99%
“…Local infiltration anesthesia (LIA) has been gaining focus in recent years, as several wellconducted studies had indicated the potential benefits postoperatively [21,22]. LIA consists of a mixture of medications that include long-acting anesthetic, NSAIDs and epinephrine.…”
Section: Anesthesia Approachmentioning
confidence: 99%
“…The limitations of the available evidence summarized in the network meta-analysis by Jiménez-Almonte et al [7] highlight the need for well-designed randomized control trials directly comparing infiltration analgesia to regional nerve blocks with respect to postoperative pain relief, opioid requirements and in-hospital duration of stay. Extrapolating from research in total knee arthroplasty, opioid requirements beyond the first 24 hours may be worth investigating: Recent data indicate that, when infiltration analgesia is used, the need for opioids is substantially reduced following the day of surgery [10]. Further unresolved issues with local infiltration analgesia include the nature and incidence of associated complications [7], the optimal composition of the solution injected [9], the injection sites best corresponding to neural anatomy [9], the application of the technique in revision surgery, and the effectiveness of the newer, long-acting liposomal bupivacaine [1].…”
Section: Where Do We Need To Go?mentioning
confidence: 99%
“…As has been the case every year for nearly two decades now, the partnership between CORR 1 and the Knee Society has produced a collection of papers that should influence thought on the most important current issues in the treatment of the adult knee. While we could feature any of the dozens of papers from those proceedings in the spotlight section, including any of several award-winners [1,3,4], we have chosen to highlight a paper by Professor Fares S. Haddad's group in the United Kingdom on a thorny and resistant topic: Single-stage exchange revision for the infected TKA.…”
Section: T Is With Great Pride That Clinicalmentioning
confidence: 99%